2020
DOI: 10.1021/acs.macromol.0c01637
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Characteristics of Polymer Brushes in Equilibrium with Solvent Vapors

Abstract: While polymer brushes in contact with liquids have been researched intensively, the characteristics of brushes in equilibrium with vapors have been largely unexplored, despite their relevance for many applications, including sensors and smart adhesives. Here, we use molecular dynamics simulations to show that solvent and polymer density distributions for brushes exposed to vapors are qualitatively different from those of brushes exposed to liquids. Polymer density profiles for vapor-solvated brushes decay more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 59 publications
(107 reference statements)
6
71
1
Order By: Relevance
“…For a single-component vapor, the absorption of a vapor depends on the strength of the interaction between this vapor and the brush . For a component in a binary vapor, this trend also holds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a single-component vapor, the absorption of a vapor depends on the strength of the interaction between this vapor and the brush . For a component in a binary vapor, this trend also holds.…”
Section: Resultsmentioning
confidence: 99%
“…Brush swelling by vapors depends on multiple system properties. In a previous study 29 from our group, simulations showed that the interparticle interactions, partial vapor pressure, and grafting density all influence the absorption of single-component vapors in contact with brushes. It was found that absorption is described relatively well by using a simple mean field model based on the Flory−Huggins theory of solvation.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The absorption isotherm of the pure brush (orange squares) is in line with isotherms found in solvophilic brushes. 23 We note that the isotherm of the bare surface (wall) has a concave rather than convex shape and that this difference contributes to the enhanced absorption, especially at low concentrations. Vapor adsorbing on a bare surface forms fewer attractive interactions with neighboring particles compared with vapor absorbing in brushes: For surfaces, these neighboring particles are located on the surface underneath the adsorbing particle, whereas for brushes, they are present around the absorbing particle.…”
mentioning
confidence: 81%
“…In fact, several studies have shown that this is a reasonable assumption for densely grafted PE brushes . Under this condition, the brush height can be expressed as , where H is the equilibrium brush height, σ g is the PE brush grafting density, N is the number of Kuhn monomers per chain, and ϕ is the PE volume fraction. Notice that ϕ is assumed to be a constant throughout the brush height, in line with the Alexander-de-Gennes model.…”
Section: Results and Discussionmentioning
confidence: 99%